1990
DOI: 10.3109/01485019008987602
|View full text |Cite
|
Sign up to set email alerts
|

Immature Spermatogenic Cells and Leucocytes in Normal and Abnormal Semen

Abstract: The frequency and ranges of the immature germinal cells (IGC) were established in 286 semen analyses from normozoospermic (group I), oligozoospermic (group 11), and azoospermic (group 111) subjects.The mean total count of IGC was greater between men from group I than between participants from groups I1 and 111. Scd spermatids were the cells most frequently observed and the spermatogonia the most unfrequently seen. Sab and Scd spermatids were the most common cells observed in group I, whereas Scd and primary sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
1
4
0
1
Order By: Relevance
“…Fedder et al [4] determined the NSpC concentration (8.6 £ 10 6 =mL and 5.7 £ 10 6 =mL) and the ratio NSpC=Sp of fertile and infertile men. His data were similar to those reported by Bassol et al [3]. Our results di er signi® cantly from those published in the last decades; however, they accord with the ® ndings of Giarola and Agostini [6].…”
Section: Discussionsupporting
confidence: 83%
“…Fedder et al [4] determined the NSpC concentration (8.6 £ 10 6 =mL and 5.7 £ 10 6 =mL) and the ratio NSpC=Sp of fertile and infertile men. His data were similar to those reported by Bassol et al [3]. Our results di er signi® cantly from those published in the last decades; however, they accord with the ® ndings of Giarola and Agostini [6].…”
Section: Discussionsupporting
confidence: 83%
“…It was even suggested that leucocytes might play a positive role in shaping the semen profile by phagocytosing morphologically abnormal spermatozoa [9], thereby attributing sperm surveillance as a normal function of male reproductive tract leucocytes [10]. It was also proposed that leucocytospermia is fully compatible with a normal semen profile as well as normal sperm function [11,12]. The validity of measuring seminal leucocytes in a routine semen analysis in pre- Simbini/Umapathy/Jacobus/Tendaupenyu/ Mbizvo dicting fertility potential was even questioned [13].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of immature germ cells in semen at different stages of spermatogenesis, has been previously documented [Bassol et al 1990;Huang and Agarwal 2004;Yeung et al 2007]. The presence of different stages of spermatogenic cells in the testis can be confirmed by the detection of certain mRNAs, exclusively expressed at a relevant maturation level [Matzuk and Lamb 2008].…”
Section: Introductionmentioning
confidence: 80%
“…Due to the limitations of these methods, application of seminal-based methods as non-invasive diagnostic tools are receiving more attention [Yatsenko et al 2006]. Immature seminal germ-cells [Bassol et al 1990;Huang and Agarwal 2004] may provide valuable information about spermatogenesis status in the testis. Koscinski et al [2005] used flow cytometry to detect low numbers of immature germ-cells in the semen of NOA patients.…”
Section: Discussionmentioning
confidence: 99%